A Comparative Perspective on the Role of Acoustic Cues in Detecting Language Structure. (22nd July 2018) - Mueller, Jutta L.; Cate, Carel ten; Toro, Juan M.
Abstract: Most human language learners acquire language primarily via the auditory modality. This is one reason why auditory artificial grammars play a prominent role in the investigation of the development and evolutionary roots of human syntax. The present position paper brings together findings from human and non‐human research on the impact of auditory cues on learning about linguistic structures with a special focus on how different types of cues and biases in auditory cognition may contribute to success and failure in artificial grammar learning (AGL). The basis of our argument is the link between auditory cues and syntactic structure across languages and development. Cross‐species comparison suggests that many aspects of auditory cognition that are relevant for language are not human specific and are present even in rather distantly related species. Furthermore, auditory cues and biases impact on learning, which we will discuss in the example of auditory perception and AGL studies. This observation, together with the significant role of auditory cues in language processing, supports the idea that auditory cues served as a bootstrap to syntax during language evolution. Yet this also means that potentially human‐specific syntactic abilities are not due to basic auditory differences between humans and non‐human animals but are based upon more advanced cognitive processes. Abstract : Mueller et al. discuss the role of acoustic cues in detecting language structure more generally. Across languages, there are clear links between acoustic cues and syntactic structure. They show that AGL experiments implementing analogous links demonstrate that prosodic cues, as well as various auditory biases, facilitate the learning of structural rules. Some of these biases, e.g. for auditory grouping, are also present in other species.